Adrenocortical Adenoma and Central Serous Chorioretinopathy: A Rare Association - S. Pastor-Idoate; D. Peña; J.M. Herreras (Case Reports in Ophthalmology, 2011)
A 28-year-old man with bilateral central serous chorioretinopathy (CSCR) and body weight gain was diagnosed with Cushing’s syndrome secondary to an adrenocortical adenoma. The patient had high levels of free cortisol and the tumor was confirmed by histopathology. After surgery, cortisol levels decreased and the CSCR spontaneously resolved. This case highlights the role of cortisol in the pathogenesis of CSCR. A diagnosis of endogenous Cushing’s syndrome should be considered in patients with CSCR as an initial symptom.